Emergency Resource Scheduling Problem Based on Improved Particle Swarm Optimation - Wu Kaijun; Shan Yazhou; Lu Huaiwei (Institute of Advanced Engineering and Science, 2014)
Emergency resource scheduling is a kind of NP combination problem which possesses important practical value. In order to overcome the problems such as long computing time and easy to fall into local best for traditional heuristic optimization algorithm, an Improved Particle Swarm Optimization algorithm (IPSO) is proposed，the algorithm uses the randomicity and stable tendentiousness characteristics of cloud model, adopts different inertia weight generating methods in different groups, the searching ability of the algorithm in local and global situation is balanced effectively. In the paper, the algorithm is used to solve the emergency resource scheduling problem, the mathematic mode is established and the solution algorithm is developed. The simulation results of example show that the algorithm has faster search speed and stronger optimization ability than GA and PSO algorithm. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5437